2020
DOI: 10.1123/apaq.2019-0185
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Motor Competence of Sex- and Age-Matched Youth With Intellectual Disability From Brazil and the United States

Abstract: Youth with intellectual disabilities (IDs) demonstrate below-criteria motor competence (MC) compared with typically developing (TD) youth. Whether differences in MC exist for youth with ID from different countries is unknown. This study examined the MC of youth with ID from Brazil (BR) and the United States (US) and compared it with norms for TD youth as established by the Bruininks–Oseretsky Test of Motor Proficiency (BOT-2). The authors measured 19 BOT-2 test items for bilateral coordination, balance, and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
1
12
1
Order By: Relevance
“…Of 19 test items from Bruininks-Oseretsky Test of Motor Proficiency-Second Edition (BOT-2) 16 involving BAL, upper limb coordination (ULC), and bilateral coordination (BLC), no significant differences existed between countries and sex (ie, Brazil males vs US males vs Brazil females vs US females) when specific motor test procedures and basic demographic factors are controlled. In addition, participants in the study by Bertapelli et al 15 had equivalent or slightly below expected BOT-2 scores for youth without disabilities in 14 of 19 test items.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Of 19 test items from Bruininks-Oseretsky Test of Motor Proficiency-Second Edition (BOT-2) 16 involving BAL, upper limb coordination (ULC), and bilateral coordination (BLC), no significant differences existed between countries and sex (ie, Brazil males vs US males vs Brazil females vs US females) when specific motor test procedures and basic demographic factors are controlled. In addition, participants in the study by Bertapelli et al 15 had equivalent or slightly below expected BOT-2 scores for youth without disabilities in 14 of 19 test items.…”
Section: Introductionmentioning
confidence: 89%
“…16 Thus, these 3 subtests best evaluate the components of motor competence. Second, although the work by Pitetti and colleagues 10,27 and Bertapelli et al 15 have established standards for the 19 items from these subtests for youth with ID without DS, it is not known if these standards can be applied to youth with DS.…”
Section: Procedures and Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As children transition to a more mature gait pattern with less variability, their balance and control in the gait cycle increases as evidenced by decreased base of support and increased step length, speed, and time in swing phase (Adolph et al, 2003; Voss et al, 2020). Gait has been used as one measure that can differentiate neurodevelopmental disorders from typical development based on these gait parameters (Lum et al, 2021; Simmons et al, 2020) Motor deficits have been identified in children with autism spectrum disorder (Gawali et al, 2017; Green et al, 2009; Provost et al, 2007), attention-deficit/hyperactivity disorder (Lee et al, 2021), cerebral palsy (Gawali et al, 2017), developmental coordination disorder (American Psychiatric Association, 2013), and in general, intellectual and developmental disabilities (Bertapelli et al, 2020; Gawali et al, 2017). In addition, motor development can be influenced by insults such as prenatal Zika virus infection (Faiçal et al, 2019; Nielsen-Saines et al, 2019; Peçanha et al, 2020) or conditions causing preterm birth (Chung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%